COMPARISON STUDY OF HEALTHY BABIES, CHILDREN AND PREGNANT WOMEN INDICATOR IN THE COASTAL MARINE AND MOUNTAIN AREA AT JEMBER DISTRICT 2015 - Sasmiyanto Sasmiyanto; Luh Titi Handayani (Faculty of Nursing, Universitas Jember, 2016)
A good nutrient status is influenced by the amount of food intake. Malnutrition status is directly influenced by food intake and infectious disease. It is also indirectly influenced by nurturing system, food availability, social, economic, culture and political factor. This research was conducted to describe condition of baby, under five years old children, and pregnant woman in coastal area and mountain range. This study was a descriptive research with cross sectional approach. There were 25 respondents in mountain area and 25 respondents in coastal area taken by purposive sampling. Data were collected through questionnaire and observational sheet of nutritional status of pregnant women, babies, and under five years old children. Result based on major assessment of nutrient status showed tendency to emaciation of babies and under five years old children in coastal area and tendency to obesity of pregnant women in coastal area. This condition was influenced by education level, family income, and knowledge of nurturing system. Weight of pregnant women should be adequate and increases according to the gestational age because the normal weight gain of mother will result in a normal weight gain of the baby. Nutrient status of pregnant woman during their developmental stage and during their pregnancy will affect fetal growth and development. Results of this research indicate that role of all sectors are needed to monitor health status by observing some aspect of nutrient status in a susceptible groups such as pregnant woman, babies and under five years old children as the target of Sustainable Goal Standard (SDGs).